2020
DOI: 10.1155/2020/8816433
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Soil Organic Carbon in Tropical Agroforests in the Churiya Range of Makawanpur, Nepal

Abstract: This paper reports the findings of a research study conducted in three tropical agroforestry systems in the Makawanpur district of Nepal, to quantify the spatial and vertical distribution of soil organic carbon in 30 cm soil profile depth in agrisilviculture, home garden, and silvopasture. The three agroforestry systems represent tropical agroforests of Nepal. It was found that the soil had 24.91 t/ha soil organic carbon in 30 cm soil profile in 2018, with 2.1% soil organic matter concentration in average. Bul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Meanwhile, UN-REDD ( 2014) indicated that REDD+ may bring between $20-86 million per year to Nepal. Additionally, most of the scientific work are concentrated on carbon and SOC stocks at different landscapes and community forest (Shrestha et al, 2004;Shrestha and Singh, 2008;Magar et al, 2020) However, there are very limited studies on soil carbon sequestration potential of community forest. Therefore, this study was intended to address the existing gap of literature by assessing the soil carbon sequestration potential of two community forests.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, UN-REDD ( 2014) indicated that REDD+ may bring between $20-86 million per year to Nepal. Additionally, most of the scientific work are concentrated on carbon and SOC stocks at different landscapes and community forest (Shrestha et al, 2004;Shrestha and Singh, 2008;Magar et al, 2020) However, there are very limited studies on soil carbon sequestration potential of community forest. Therefore, this study was intended to address the existing gap of literature by assessing the soil carbon sequestration potential of two community forests.…”
Section: Introductionmentioning
confidence: 99%
“…Tropical agroforests have been found to play a significant part in storing organic carbon content in the soil. The total amount of organic carbon in the soil was discovered to be 24.91 tonnes per hectare (Magar et al, 2020). Agroforestry provides an approach through which in very little time organic content could be added by selection of proper nitrogen-fixing tree species and if they are fast-growing too (Tsufac et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Trees in agroforestry systems improve soil organic matter, N-retention, water holding capacity and infiltration rates in the soil. They help in the preservation of soil fertility through nitrogen fixation and return of organic content through leaf fall (Rosenstock et al, 2014).Soil is the biosphere's greatest reservoir of terrestrial organic carbon; it contains more carbon than the atmosphere in combination with the plants (Magar et al, 2020). The presence of agricultural systems optimizes recycling of nutrients which results in tree species having a positive effect on various soil properties.…”
Section: Introductionmentioning
confidence: 99%
“…An ideal structure for soils to support crop growth must have aggregate size between 1 to 10 mm diameter. These aggregates should be stable when wet and have a good proportion of pores with diameter greater than 75µm to promote good aeration and drainage and at the same time provide an adequate volume of medium sizes pores (30 -0.2 µm) to store available water [2]. Deforestation and cultivation practices caused fragmentation in soil aggregates due to rapid wetting, and the direct impact of tillage practice which exposed protected soil organic matter to microbial attack [3].…”
Section: Introductionmentioning
confidence: 99%
“…In deforested tropical areas with highly weathered soils, less issues were observed in soil physical properties dynamics [2]. Previous research on Sumatra island show that soil physical properties are the most sensitive indicators when detecting the impact of cultivation and deforestation [4].…”
Section: Introductionmentioning
confidence: 99%